COMMUNICATION STRATEGIES EMPLOYED BY THE ELT STUDENTS IN SPEAKING CLASS - Rozal, Edi (State Islamic University of Sulthan Thaha Saifuddin Jambi, 2017)
This study was aimed at identifying the communication strategies employed by the students in Speaking class and their reasons in employing communication strategies. The designof the research was descriptive case study. The result of the study shows that the students employed twelve communication strategies, namely, approximation strategy which was employed by the students 65 times, stalling or time-gaining 44 times, appeal for help 19 times, literal translation 15 times, code switching 13 times, message abandonment 10 times, topic voidance 7 times, word coinage twice, foreignizing once, use of non-linguistic signals once, repetition 25 times, andself-correction 5 times. Based on the data obtained from the interview, the researcher found that the students who used communication strategies said that they used communication strategiesbecause of their nervousness, lack of vocabulary, lack of language structures, the influence of their L1. Moreover, the students said that they wanted to avoid the silence of speaking, to make the word clear to the listener and to correct their own mistakes. Â Keywords:speaking class, communication strategy, types of communication strategies Â